Clinical approach for diagnosing chronic kidney disease based on a series of cases in dogs - Tovar, A.M.F.R. [UNESP]; Carvalho, M.B. [UNESP]; Silva, G.S. [UNESP]; Bizare, A. [UNESP] (FapUNIFESP (SciELO), 2025)
ABSTRACT Chronic kidney disease (CDK) is the condition most frequently diagnosed in nephrology in dogs. CDK is progressive and irreversible, but the patient can be treated to decrease the rate of progression and improve the quality of life. All CKD cases originate from some type of kidney injury (underlying disease), which can be eventually diagnosed and subject to therapeutic intervention. The present prospective study aimed to evaluate dogs referred to check-up or for showing any signs suggestive of kidney disease. The study included 129 dogs, of which 34 had no kidney disease (control group) and 95 had CDK. Among the patients with CDK, 17 CDK 1, 36 CDK 2, 23 CDK 3, and 19 CDK 4 were found, according to staging criteria of the IRIS staging of CDK-2023. The test carried out made possible the clinical diagnosis of four categories of underlying kidney disease (congenital nephropathy, glomerular or tubule-interstitial disease, glomerulopathy and pyelonephritis). The present study may contribute as an illustration of the diversity of CDK manifestations in dogs, and their implications for the selection of priority laboratory tests for clinical practice. RESUMO A doença renal crônica (DRC) é a condição mais frequentemente diagnosticada na nefrologia e na urologia em cães. A DRC é progressiva e irreversível, mas o paciente pode ser tratado tendo como objetivo reduzir a taxa de progressão e melhorar a qualidade de vida. Todos os casos de DRC se originam de algum tipo de lesão renal (doença de base), que pode ser eventualmente diagnosticada e passível de intervenção terapêutica. O estudo teve como objetivo avaliar cães encaminhados para check-up ou com algum sinal sugestivo de doença renal. Foram incluídos 129 cães, dos quais 34 não tinham doença renal e 95 apresentavam DRC. Entre os pacientes com DRC, encontram-se 17 DRC 1, 36 DRC 2, 26 DRC 3 e 19 DRC 4, de acordo com os critérios de estadiamento da Sociedade Internacional de Interesse Renal (IRIS)- 2023. Os exames realizados possibilitaram o diagnóstico clínico de quatro categorias de doença renal de base (nefropatias congênitas, doença glomerular ou túbulo intersticial, glomerulopatia e pielonefrite). Este estudo pode contribuir como ilustração sobre a diversidade de manifestações da DRC em cães e suas implicações para seleção dos exames laboratoriais prioritários para a prática clínica.